The Influence of Media Exposure, Slack Resources, Public Ownership and Profitability on Corporate Social Responsibility Disclosure - Estuningsih Leandra Endhita (Journal of Applied Accounting and Sustainable Finance, 2025)
Purpose – This study aims to determine the influence of Media Exposure, Slack Resources, Public Ownership, and Profitability on Corporate Social Responsibility Disclosure.  Design/methodology/approach – This study uses quantitative data, the sample in this study is 55 non-cyclical consumer companies listed on the Indonesia Stock Exchange in the period 2018-2022. The analysis techniques used to test the hypothesis are statistical analysis, namely: descriptive statistics, classical assumption tests (normality, multicollinearity, heterokedasticity, and autocorrelation), multiple linear analysis, hypothesis tests and determination coefficients with SPSS 25.0.  Findings – The results of this study show that the Media Exposure variable has a positive and significant effect on corporate social responsibility disclosure, the slack resources variable has a negative and insignificant effect on corporate social responsibility disclosure, the public ownership variable has a positive and insignificant effect on corporate social responsibility disclosure, and the profitability variable has a positive and significant effect on corporate disclosure social responsibility. Originality/value - This study discusses Corporate Social Responsibility Disclosure and other factors such as Media Exposure, Slack Resources, Public shareholding and Profitability focusing on consumer non-cyclical. This study uses the Sustainbility Reporting Guidelines (SRG) index. Launched by the Global Reporting Initiative (GRI), in the SRG, there are 79 items spread across 6 performance indicators.